Nonorthogonal unitaries in two-way quantum key distribution - Shamsul Shaari, Jesni (Elsevier, 2014)
Two-way Quantum Key Distribution (QKD) schemes commonly make use of a set of unitaries corresponding to binary encodings which can in principle be distinguished perfectly. In this paper, inline with the proposal in Chiribella et al. (2008) [13], we introduce a non-entangled two-way QKD scheme with two sets of unitaries of which the elements in one set can be viewed as ‘nonorthogonal’ to elements in the other with the aim of naturally suppressing an eavesdropper's information to provide for a higher security threshold. Security analysis is done in the context of individual attack strategies for a quick comparison with the conventional two-way QKD scheme. Given the richer structure of the improvement, future direction is also discussed.